2016
DOI: 10.1103/physrevfluids.1.054302
|View full text |Cite
|
Sign up to set email alerts
|

Time-reversal of nonlinear waves: Applicability and limitations

Abstract: Time-reversal (TR) refocusing of waves is one of fundamental principles in wave physics. Using the TR approach, "Time-reversal mirrors" can physically create a time-reversed wave that exactly refocus back, in space and time, to its original source regardless of the complexity of the medium as if time were going backwards. Lately, laboratory experiments proved that this approach can be applied not only in acoustics and electromagnetism but also in the field of linear and nonlinear water waves. Studying the rang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…In this section, we will recall the main results of previous studies (Chabchoub & Fink 2014;Ducrozet et al 2016b) that have demonstrated the possibility of the use of a TR mirror to refocus extreme water waves obtained from analytic solutions to the NLSE in a water-wave facility. The TR procedure is briefly explained, followed by a description of the different rogue wave profiles used in the study.…”
Section: Methodology and Experimental Set-upmentioning
confidence: 99%
See 4 more Smart Citations
“…In this section, we will recall the main results of previous studies (Chabchoub & Fink 2014;Ducrozet et al 2016b) that have demonstrated the possibility of the use of a TR mirror to refocus extreme water waves obtained from analytic solutions to the NLSE in a water-wave facility. The TR procedure is briefly explained, followed by a description of the different rogue wave profiles used in the study.…”
Section: Methodology and Experimental Set-upmentioning
confidence: 99%
“…At first, we define time-series ramps at the beginning and end of the chosen time window in order to ensure (i) a smooth initialization of the wavemaker's movement and (ii) the periodicity of the signal, which is decomposed on Fourier components. Then, the effective motion is defined using a linear transfer function to initiate the wave profiles (Chabchoub & Fink 2014;Ducrozet et al 2016b). This latter linearization has been identified as a possible source of inaccuracy in the TR procedure.…”
Section: Wave Generationmentioning
confidence: 99%
See 3 more Smart Citations